Gastric Adenocarcinoma with Systemic Metastasis Involving the Intraocular Choroid and Duodenum - Soon Young Kim; Kee-Taek Jang; Jun Haeng Lee (Korean Society of Gastrointestinal Endoscopy, 2018)
Gastric cancer with double metastasis to the orbit and duodenum is extremely rare. We report the case of a patient with gastric adenocarcinoma who presented with synchronous orbital and duodenal metastases at the time of initial diagnosis. A 60-year-old man presented with a 1-month history of visual disorder and pain in his right eye. He underwent ophthalmological examinations. The biopsy results suggested intraocular metastatic carcinoma. We conducted a systemic evaluation to identify primary malignancy. Finally, a diagnosis of advanced gastric adenocarcinoma with multi-organ metastasis was made. He planned to be treated with systemic chemotherapy.